Impact of fiscal institutions on public finances in the European Union: Review of evidence in the empirical literature - Martin Gorčák; Stanislav Šaroch (Review of Economic Perspectives, 2021)
This paper examines the impact of budgetary institutions on public finances in the European Union on the basis of a critical survey of the relevant theoretical and empirical literature. In general, the authors find that fiscal institutions (namely fiscal rules) have successfully contributed to greater fiscal sustainability, reduced procyclicality of fiscal policies within the EU, and increased national ownership of fiscal rules by strengthening national fiscal frameworks. A fiscal reaction function was one of the widely used methods to determine the principal variables affecting fiscal outcomes. Some authors used cyclically-adjusted fiscal outcomes as the dependent variable representing the discretionary fiscal policy-making whereas others put emphasis on other fiscal outcomes. The samples of countries covered mostly the EU Member States, representing rather homogenous samples in the context of common EU fiscal framework. Institutional aspects used as independent variables differed significantly among authors and some could be added for future research. Based on the literature survey, several recommendations were made for fiscal policy-making.
Keywords: E61; E62; H61; H62; H63; 330; Deficit Bias; European Fiscal Framework; Fiscal Governance; Fiscal Institutions; Fiscal Outcomes; Fiscal Rules; Stability and Growth Pact